2022
DOI: 10.3389/fmed.2022.926573
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasound in Temporomandibular Joint Disorders: An Update and Future Perspectives

Abstract: Temporomandibular joint (TMJ) disorder is the second most common chronic pain condition affecting the general population after back pain. It encompasses a complex set of conditions, manifesting with jaw pain and limitation in mouth opening, influencing chewing, eating, speaking, and facial expression. TMJ dysfunction could be related to mechanical abnormalities or underlying inflammatory arthropathies, such as rheumatoid arthritis (RA) or juvenile idiopathic arthritis (JIA). TMJ exhibits a complex anatomy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 111 publications
1
17
0
2
Order By: Relevance
“…8,45,46 US can also be suggested as useful examination tool due to its widespread accessibility, cost-effectiveness, real-time quick dynamic and direct assessment and higher paediatric patient tolerance with no need of sedation or use of contrast, the potential utility in detecting both osteochondral and soft-tissue changes during imageguided TMJ procedures and for monitoring the course of a pathological condition or treatment. 43,47 However, besides the US limitations there are no reference values of lateral condylar changes, synovial or capsular-condylar thickness or joint effusion neither an accepted scoring system of these TMJ measurements. [48][49][50] The correlation between US and contrast-enhanced MRI in children with JIA is positive and evaluate as 'moderate' when considering the acute arthritis visualised as synovial enhancement or increased capsular and lateral periarticular space.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8,45,46 US can also be suggested as useful examination tool due to its widespread accessibility, cost-effectiveness, real-time quick dynamic and direct assessment and higher paediatric patient tolerance with no need of sedation or use of contrast, the potential utility in detecting both osteochondral and soft-tissue changes during imageguided TMJ procedures and for monitoring the course of a pathological condition or treatment. 43,47 However, besides the US limitations there are no reference values of lateral condylar changes, synovial or capsular-condylar thickness or joint effusion neither an accepted scoring system of these TMJ measurements. [48][49][50] The correlation between US and contrast-enhanced MRI in children with JIA is positive and evaluate as 'moderate' when considering the acute arthritis visualised as synovial enhancement or increased capsular and lateral periarticular space.…”
Section: Discussionmentioning
confidence: 99%
“…36,46 The disc position was not checked in any of the included studies probably because previous outcomes on patients with TMD were confusing. Only a few authors observed some abnormalities in the disc-condyle relationship through US, 43,[51][52][53][54][55] however, it is overall accepted that US is not useful neither accurate to diagnose TMJ disc displacements 36,43,[56][57][58][59][60] when a discrimination between displacement with or without reduction is needed. 43,54 About the detection of intraarticular effusion in the TMJ area, Manfredini et al 54 stated that US remains potentially useful as an alternative imaging technique with a good accuracy, 48 even though the challenging analysis of TMJ capsular width is in only 2 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations